Iron Deficiency Is Associated With Impaired Myocardial Reperfusion in ST‐Segment–Elevation Myocardial Infarction: Influence of the Definition Used - José A. Barrabés; Javier Inserte; Laura Castellote; Irene Buera; Laia Milà; Antonia Sambola; Aitor Uribarri; Maria Vidal; David Aluja; Sara Delgado‐Tomás; Pablo E. Tobías‐Castillo; Maria Calvo‐Barceló; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background The role of iron deficiency (ID) in ST‐segment–elevation myocardial infarction (STEMI) remains unclear. This study aimed to assess whether ID is associated with impaired myocardial reperfusion in STEMI and whether this association is affected by ID definition. Methods We included 942 consecutive patients with STEMI successfully treated with primary percutaneous coronary intervention. ID was defined either as recommended by international guidelines or, alternatively, as ferritin <100 ng/mL, transferrin saturation <20%, or serum iron ≤13 μmol/L. In 595 patients, serum soluble transferrin receptor levels were measured. Impaired myocardial reperfusion was defined as lack of ST‐segment resolution ≥50% 60 to 90 minutes after percutaneous coronary intervention. Results ID prevalence varied across these definitions. Impaired reperfusion was present in 12.7% of patients without ID and 41.0% of those with ID defined by transferrin saturation <20% (P<0.001). This association was less pronounced for serum iron ≤13 μmol/L, weaker for guideline criteria, and absent for high (≥1.59 mg/L) soluble transferrin receptor levels or low ferritin. Transferrin saturation <20%, but not ferritin‐based criteria, was associated with poorer clinical course and left ventricular function and higher in‐hospital mortality and remained an independent predictor of impaired reperfusion after adjusting for baseline predictors and anemia. Conclusions ID defined by transferrin saturation <20% is strongly related to impaired ST resolution and predicts a worse in‐hospital outcome in patients with STEMI treated with primary percutaneous coronary intervention. The association of other ID criteria with myocardial reperfusion or with the clinical course is weaker or absent. The potential preventive or therapeutic strategies targeting ID in STEMI warrant further investigation.